Two projection methods for solving the multiple-set split common null point problem in Hilbert spaces. (1st September 2020) - Reich, Simeon; Tuyen, Truong Minh
ABSTRACT: We study the multiple-set split common null point problem in two Hilbert spaces. In order to solve this problem, we propose two new parallel algorithms and establish strong convergence theorems for both of them. Our schemes combine the hybrid and shrinking projection methods with the proximal point algorithm.